The role of flavonoids in the treatment of periodontal diseases – literature review - Jakub Adamczyk; Martyna Chwałowska; Natalia Gębka; Krzysztof Stós; Natalia Jakubowicz; Agnieszka Gabryś-Kwolek; Rafał Rój (Journal of Pre-Clinical and Clinical Research, 2022)
Introduction and objective Periodontal disease is one of the many diseases of the oral cavit. Periodontium is defined as the tissues that surround and hold the tooth in the socket. Periodontitis may lead to the loss of hard and soft tissues, resulting in the loss of dentition. The current standards for the treatment of periodontal disease are based on both surgical treatment and non-surgical treatment. The subject of research among many scientists is the effect of flavonoids – substances of plant origin, on periodontal diseases. This literature review aims to present the possibility of using flavonoids as adjunctive treatment in periodontal diseases.